Phonological abilities in Persian preschool children with stuttering and fluent peers - Tahmasebi, Neda; Ahmadi, Akram; Zamani, Peyman; Nourafshan, Mozhgan; Salehimanesh, Farzaneh (Iranian Journal of Child Neurology, 2019)
Objectives Speech sound production is poorer in stutterers than normally fluent peers. This study was performed to compare speech sound production abilities in Persian speaking children with developmental stuttering. Materials & Methods Overall, 34 children with stuttering and 60 children without stuttering aged from 3 to 6 yr old were enrolled from Ahvaz City, Khuzestan Province, southern Iran in 2016. The phonetic information test was used to assess speech sound production in this study and 30-minute mother-child conversations were utilized for calculation of Percentage Consonant Correct. Phonological abilities of these two groups were compared against each other and a correlation between stuttering severity and speech sound articulation was calculated. Results There was significant difference between children with stuttering and normal peers for articulation error total percentage but not significant difference was found for percentage consonant correct (P=0.16). Moreover, no significant correlation between stuttering severity and speech sound production in this population was found. Conclusion No association seems to exist between stuttering severity and speech sound production abilities in this population. This study may lead to the notion that there was significant difference between the two groups in speech sound production assessment.